Bark traits and life‐history strategies of tropical dry‐ and moist forest trees. (10th September 2013) - Poorter, Lourens; McNeil, Adam; Hurtado, Victor‐Hugo; Prins, Herbert H. T.; Putz, Francis E.; Kitajima, Kaoru
Summary Bark is crucial to trees because it protects their stems against fire and other hazards and because of its importance for assimilate transport, water relationships and repair. We evaluate size‐dependent changes in bark thickness for 50 woody species from a moist forest and 50 species from a dry forest in Bolivia and relate bark thickness to their other bark characteristics, species life‐history strategies and wood properties. For 71% of the evaluated species, the allometric coefficient describing the relationship between bark thickness and stem diameter was significantly <1 (average 0·74; range 0·38–1·20), indicating that species attain an absolute increase in bark thickness with increasing stem diameter but invest relatively less in bark thickness at larger diameters. We hypothesized that in response to more frequent fires, dry‐forest species should have thicker barked trees. Contrary to this prediction, dry‐ and moist‐forest tree species were similar in allometric bark coefficients and bark thickness. In both forest types, about 50% of the species never developed bark thick enough to avoid fire damage to their vascular cambia. Recent increases in fire frequency and extent may therefore have potentially large effects on the composition of these forests. Within each forest, coexisting species displayed a diversity of bark investment strategies, and bark thickness of trees 40 cm stem diameter varied up to 15‐fold across species (ranging from 1·7 to 25·7 mm). In both forests, sapling bark thickness was positively related to adult stature (maximum height) of the species, possibly because trees of long‐lived species are more likely to experience fire during their life span, whereas for species that are characteristically small or short‐lived, it may not pay off to invest heavily in bark and they may follow a resprouter strategy instead. Sapling bark thickness was not related to species' shade tolerance. Bark and wood traits were closely associated, showing a trade‐off between species with tough tissues (high densities of bark and wood) on the one hand vs. species with watery tissues (high water contents of bark and wood) and thick bark on the other hand. Species with different bark investment strategies coexist in both the moist and the dry tropical forest studied. Bark and wood fulfil many functions, and the observed trade‐offs may reflect different plant strategies to deal with fire, avoidance and repair of stem damage, avoidance and resistance of drought stress, and mechanical stability.